The impact of the UK new deal for lone parents on benefit receipt - Peter Dolton; Jeffrey A. Smith (Institute for the Study of Labor (IZA), 2011)
This paper evaluates the UK New Deal for Lone Parents (NDLP) program, which aims to return lone parents to work. Using rich administrative data on benefit receipt histories and a selection on observed variables identification strategy, we find that the program modestly reduces benefit receipt among participants. Methodologically, we highlight the importance of flexibly conditioning on benefit histories, as well as taking account of complex sample designs when applying matching methods. We find that survey measures of attitudes add information beyond that contained in the benefit histories and that incorporating the insights of the recent literature on dynamic treatment effects matters even when not formally applying the related methods. Finally, we explain why our results differ substantially from those of the official evaluation of NDLP, which found very large impacts on benefit exits.
urn:nbn:de:101:1-201104113642
Keywords: I3; 330; program evaluation; active labor market policy; matching; lone parents; New Deal; Arbeitsmarktpolitik; Aktivierende Sozialhilfe; Reform; Alleinerziehende; Sozialhilfeempfänger; Wirkungsanalyse; Berufliche Integration; Großbritannien